'The Stone Sky': Dwelling and habitation in other worlds. Issue 2 (1st December 2014) - Grant, Jane
Have humans always had the desire to inhabit other worlds? From the microscopic scale to the vastness of outer space, it seems our capacity for occupying uninhabitable spaces with our intellect, our bodies, our sensorium, our desire, is fundamental to our being.What are these spaces and how do we come to 'know' them? Whether mythological, religious or scientific, these minute or vast worlds are spaces that we unfold, narrate and dwell in. In his short story 'The Stone Sky' the novelist Italo Calvino writes of the inhabitants who live in a world that exists beneath the earth's crust. These inhabitants who occupy the underworld exist in a mutable form that allows them to travel through the dense, dark inner landscape of the earth, through the crystal structures, the nickel sea to the earth's core, an intricate viscous landscape quite other than the formation of matter on the earth's surface. Calvino's narration tells us of what is it to inhabit the interstices of the underworld, to be in a space with little intervening air, to live within the deep time scale of crystal formation. The neuroscientist Christof Koch states that 'we live in a universe where organised bits of matter give rise to consciousness' and that we need to extend our understanding of what consciousness really is. Could it be that these other worlds, whether planets only just glimpsed through early telescopes, or nano-landscapes at the scale of the atom are still integrated with our own fundamental make-up? Are they the product of a vastly developed pre-frontal cortex or are they a result of ideas, knowledge and experiences accumulated over billions of years? In this article I will look at the concepts of matter as a carrier of consciousness and of panpsychism as a tool with which to understand our habitation of other worlds.